Social Correlates of Aging and Quality of Life of Older Adults in Rural and Urban Areas of Southwestern Nigeria: A Comparative Cross-Sectional Study (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Quality of Life (QoL) among older adults is an important area of concern that directly affects their health status and wellbeing. This study was conducted to investigate and compare the social correlates influencing the Quality of Life (QoL) among older adults in rural and urban areas of Oyo State, Southwestern Nigeria. A comparative study of 958 older adults was conducted using a two-stage cluster sampling technique. A semi-structured, interviewer-administered questionnaire was used to elicit information on QoL and social security. QoL was assessed using a WHO QoL-BREF questionnaire. Twenty-six questions on a Likert scale of 1-5 gave a minimum and maximum obtainable score of 26 (20%) and 130 (100%), respectively. QoL was dichotomized into good or poor using an average of 3 and above (≥78/130; ≥60%) as good QoL and scores below 3 (